Migration Control and Access to Welfare The Precarious Inclusion of Irregular Migrants in Norway - Karlsen, Marry-Anne (On Edge: Ethnographies and Theories of Threshold Phenomena, 2020)
Over the past decades, European states have increasingly limited irregular migrants' access to welfare services as a tool for migration control. Still, irregular migrants tend to have access to certain basic services, although frequently of a subordinate, arbitrary, and unstable kind. Drawing on in-depth ethnographic fieldwork conducted in Norway, this book sheds light on ambiguities in the state's response to irregular migration that simultaneously cut through law, policy, and practice. Carefully examining the complex interplay between the geopolitical management of territory and the biopolitical management of populations, the book argues that irregularised migrants should be understood as precariously included in the welfare state rather than simply excluded. The notion of precarious inclusion highlights the insecure and unpredictable nature of the inclusive practises, underscoring how limited access to welfare does not necessarily contradict restrictive migration policies. Taking the situated encounters between irregularised migrants and service providers as its starting point for exploring broader questions of state sovereignty, biopolitics, and borders, Migration Control and Access to Welfare offers insightful analyses of the role of life, territory, and temporality in contemporary politics. As such, it will appeal to scholars of migration and border studies, gender research, social anthropology, geography, and sociology.